Tracking children's learning chart: Addition and subtraction - National Strategies
This chart tracks children's learning in addition and subtraction. The tracking charts act as an initial diagnostic tool and a background framework for the sets of teaching materials referenced to common misconceptions and errors. This chart forms part of the Supporting children with gaps in their mathematical understanding set of materials.
Keywords: _C:United Kingdom GBR